2001
DOI: 10.1074/jbc.m006231200
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of ω-6-Oleate Desaturase Deficiency on Lipid Dynamics and Functional Properties of Mitochondrial Membranes ofArabidopsis thaliana

Abstract: We probed the role of the polyunsaturated fatty acids on the dynamic and functional properties of mitochondrial membranes using the fad2 mutant of Arabidopsis thaliana, deficient in -6-oleate desaturase. In mitochondria of this mutant, the oleic acid content exceeded 70% of the total fatty acids, and the lipid/protein ratio was greatly enhanced. As a consequence, local microviscosity, probed by anthroyloxy fatty acid derivatives, was increased by 30%, whereas the lipid lateral diffusion, assayed using 1-pyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…We took advantage of two mutant Arabidopsis cell lines, fad2 and Fad3 1 , which are affected in their fatty acid desaturases. The 18:1 desaturase is shut down in the fad2 mutant (Okuley et al, 1994), resulting in an accumulation of 18:1 fatty acids (Caiveau et al, 2001), whereas the Fad3 1 mutant accumulates 18:3 fatty acids (Shah et al, 1997). Given the important role played by lipids with saturated fatty acyl chains in regulating the physicochemical properties of biological membranes, it was particularly interesting to check DRM formation in these two cell lines, which exhibit significant differences in the mean fluidity (defined as temperaturedependent lipid movements in the membrane) of their PM, compared to the PM of wild-type cells (Vaultier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We took advantage of two mutant Arabidopsis cell lines, fad2 and Fad3 1 , which are affected in their fatty acid desaturases. The 18:1 desaturase is shut down in the fad2 mutant (Okuley et al, 1994), resulting in an accumulation of 18:1 fatty acids (Caiveau et al, 2001), whereas the Fad3 1 mutant accumulates 18:3 fatty acids (Shah et al, 1997). Given the important role played by lipids with saturated fatty acyl chains in regulating the physicochemical properties of biological membranes, it was particularly interesting to check DRM formation in these two cell lines, which exhibit significant differences in the mean fluidity (defined as temperaturedependent lipid movements in the membrane) of their PM, compared to the PM of wild-type cells (Vaultier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their deficit in 18:1 desaturase (Okuley et al, 1994), fad2 cells accumulate fatty acyl chains enriched in 18:1 (Caiveau et al, 2001), whereas the Fad3 1 mutant accumulates 18:3 fatty acids (Shah et al, 1997).…”
Section: Impact Of the Fatty Acid Unsaturation Degree On Lipid Microdmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane Potential and Oxygen Consumption-Membrane potential was measured continuously and simultaneously to oxygen consumption using a tetraphenylphosphonium (TPP ϩ )-sensitive electrode in the presence of 4 M TPP ϩ and a Clark-type oxygen electrode at 20°C (14). The membrane potential values were calculated using the equation of Kamo et al (15) (16).…”
Section: Methodsmentioning
confidence: 99%
“…Mutations for FAD2 and FAD5 desaturases impair plant growth under low temperature, and fad2 mutant plants show a much more severe phenotype than the fad5 mutant under low temperature growth (Kunst et al, 1989;Hugly and Somerville, 1992;Miquel et al, 1993). The FAD2 mutation abolishes 18:1 desaturation in the ER pathway, thus reducing desaturation of ER-derived MGDG and DGDG in the plastid and desaturation of mitochondrial membrane lipids, including PC, PE, DPG, PI, and PG (Caiveau et al, 2001). In this study, we found that the ADS2 mutation resulted in higher 16:0 and 18:0 and lower 16:3 and 18:3 content under 6°C growth conditions, indicating that ads2 mutant plants lose their ability to increase FA desaturation in response to low temperature exposure (Table 1).…”
Section: Association Of Fa Desaturation With Cold and Freezing Tolerancementioning
confidence: 99%